A Comparative Analysis in Vehicle Taxation - Álvarez, Montserrat Hermosín (Revista Amagis Jurídica, 2024)
CONTENTS . 1. Introduction. Framework. 1.1. Vehicles: a manifestation of wealth generally taxed by EU Member States. 1.2. Two broad categories: vehicle ownership taxes and registration taxes. 1.3. Huge vehicle taxation interstate disparities. 2. Proposal for a council directive on taxes on passenger cars of 5 july 2005. 3. Vehicle registration tax trends followed by member states. 3.1. Member States that do not require vehicle registration taxes. 3.2. Member States that do not take environmental elements into account. Taxation depends on technical elements of the vehicle. 3.3. Estados miembros que mantienen el Impuesto de Matriculación con la incorporación de elementos medioambientales. 4. Vehicle ownership or road tax trends followed by member states. 4.1. Member States that use the mechanical elements of vehicles as a basis for taxation. 4.2. Member States introducing environmental elements into the road tax quantification. 4.3. Environmental road taxes. 5. Evolution of vehicle taxation policies: a comparative analysis across OECD countries. 5.1. Introduction. 5.2. Taxes on sale and registration of motor vehicles. 5.3. Periodic taxes payable in connection with the ownership or use of the vehicles. 6. Final reflections. 6.1. Profound differences among OCDE and EU Member State tax systems. 6.2. A necessary green reformulation of vehicle registration and road taxes: the "polluter pays" principle. 6.3. Tax quantification based on emitted CO 2 . Bibliography.